Importance of Arabic linguistics in Islamic jurisprudence. - Kurmanbayev., K. (Journal of Oriental Studies, 2016)
This article discusses the importance of Arabic linguistics to extract legal rules of Islamic jurisprudence and its influence on the various points of view of scientists.